Measuring Social Enterprise Value Creation: The Case of Furniture Bank. Issue 2 (12th November 2015) - Mook, Laurie; Chan, Andrea; Kershaw, Dan
Abstract : This article presents a case study that explores the creation of value by a social enterprise, Furniture Bank, for its stakeholders. The study is undertaken using the social return on investment framework. The case highlights insights and caveats that resulted from undertaking this type of analysis. This article calls for an integrated approach to social return on investment processes, incorporating both conventional accounting and social accounting.